The Nurturing Gen Z’s Potential: A Multidimensional Approach to Preparing for an AI-Driven Future - Lhakard, Polwasit (Journal of Modern Learning Development, 2024)
This research investigates the strengths and vulnerabilities of Generation Z in relation to an AI-driven future and proposes a multidimensional framework for their development. The study focuses on individuals born between the mid-1990s and early 2010s. Surveys, interviews, and observations are used as research instruments to gather data. Findings reveal that Generation Z possesses a high level of technological nativity, but there is a need to enhance their critical digital literacy. They demonstrate adaptability to change, but striking a balance between surface-level versatility and deep learning is necessary. While they collaborate effectively with AI tools, they require a critical understanding of biases, limitations, and ethical implications associated with AI systems. This research emphasizes the importance of integrating AI education into school curricula, fostering critical thinking and creativity, promoting digital well-being, and addressing ethical considerations. A multidimensional approach involving educators, policymakers, and researchers is vital to empower Generation Z as critical thinkers, creative problem-solvers, and responsible users of AI. These findings contribute to the successful integration of Generation Z into the AI-driven society of tomorrow.